2011
DOI: 10.1097/mpa.0b013e3182061583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Obesogenic Diets on Pancreatic Histology in Ossabaw Miniature Swine

Abstract: Objective Obesity is a factor in the outcome and severity of pancreatic conditions. We examined the effect of hypercaloric diets on the pancreata of Ossabaw swine, a large animal model of metabolic syndrome and obesity. Methods Swine were fed with 1 of 4 diets: high-fructose (n = 9), atherogenic (n = 10), modified atherogenic (n = 6), or eucaloric standard diet (n = 12) for 24 weeks. Serum chemistries were measured, and pancreata were examined for histological abnormalities including steatosis, inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Additionally, animal studies have observed that fructose intake may play a role in the development of local fat depots. [55][56][57] To date, however, no study in humans has examined the effects of sugar on local ectopic depots, including such sites as the kidney, pancreas, heart, and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, animal studies have observed that fructose intake may play a role in the development of local fat depots. [55][56][57] To date, however, no study in humans has examined the effects of sugar on local ectopic depots, including such sites as the kidney, pancreas, heart, and blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Ossabaw swines, another animal model for the MetS, pancreatic steatosis was not associated with other histological abnormalities[20]. …”
Section: Clinical Significancementioning
confidence: 99%
“…Swine MetS has provided insight regarding obesity-induced alterations in the central nervous system, (Karmi et al , 2010) digestive system, (Liang et al , 2015) pancreas, (Fullenkamp et al , 2011) gut microbiome, (Pedersen et al , 2013) heart, (Neeb et al , 2010) kidney, (Li et al , 2011) reproductive, (Newell-Fugate et al , 2014) and musculoskeletal (Karmi et al , 2010) systems, as well as metabolic health in the offspring. (Arentson-Lantz et al , 2014) On the other hand, the higher cost of large compared to small animals may limit the experimental sample size, and assessment of central obesity in swine is limited by missing firm standards for waist circumference or body-mass index.…”
Section: Inducing Mets In Swinementioning
confidence: 99%